2019
DOI: 10.1177/1098612x19872428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of signalment, clinical, laboratory and radiographic parameters in cats with feline asthma and chronic bronchitis

Abstract: Objectives Feline asthma (FA) and feline chronic bronchitis (CB) are common respiratory conditions in cats, frequently referred to as ‘feline lower airway disease’. However, the aetiologies of both inflammatory airway diseases are probably different. Little is known about the differences in signalment, clinical signs, laboratory abnormalities and radiographic features between cats with these two airway diseases. The aim of the study was to investigate whether certain parameters can help in differentiating betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 33 publications
4
26
1
2
Order By: Relevance
“…Clinical examination is commonly used as the most important diagnostic tool to evaluate response to therapy in cats with FLAD [ 9 ]. In this study, the majority of cats showed coughing as a presenting complaint, which is consistent with previous reports [ 11 , 17 , 38 , 51 ]. Abnormal respiratory sounds were described as frequently as coughing.…”
Section: Discussionsupporting
confidence: 93%
“…Clinical examination is commonly used as the most important diagnostic tool to evaluate response to therapy in cats with FLAD [ 9 ]. In this study, the majority of cats showed coughing as a presenting complaint, which is consistent with previous reports [ 11 , 17 , 38 , 51 ]. Abnormal respiratory sounds were described as frequently as coughing.…”
Section: Discussionsupporting
confidence: 93%
“…Asthma or eosinophilic bronchitis is one of the most prevalent pulmonary diseases in cats [9]. However, there are other feline chronic lower airway diseases that course with broncho-reactivity such as chronic bronchitis, bacterial bronchopneumonia, viral pneumonia, parasitism pneumonia, fungal pneumonia, intrathoracic neoplasia, Mycoplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…felis is an infectious agent present in a subset of cats with chronic suppurative bronchitis, it is not possible to make any inferences on the importance of F . felis in cats with florid eosinophilic bronchitis (feline asthma), as our cohort of cats was largely devoid of such cases due to selection bias in obtaining BALF from cats thought not to have primary allergic airway disease [ 35 , 36 ]. Although it was logical to concentrate on such cases to search for cryptic feline pathogens, the omission of classical feline asthma BALF specimens means we can make no inference on the extent to which F .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even higher numbers of cats might be affected as respiratory distress and coughing can be misidentified as 'a hairball problem' by owners, so the actual prevalence of airway disease is probably under-estimated [34]. Feline bronchial disease can be further classified into four overlapping categories-(i) feline asthma, characterised by eosinophilic airway inflammation associated with increased mucus, bronchospasm, coughing and distal air trapping, (ii) chronic bronchitis, where neutrophils are the predominant cell type within airways and coughing is the main clinical sign [33][34][35][36], (iii) parasitic bronchitis, and (iv) secondary bacterial bronchitis [37]. A key distinguishing feature of asthma is reversible airflow limitation due to functional bronchoconstriction, thought to result from a type I hypersensitivity reaction in airway walls associated with mast cell degranulation [33,34,38].…”
Section: Introductionmentioning
confidence: 99%